YIB TRAINING STUDENTS THE ESSENTIALS OF SCIENCE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 21 August 2016 - The Youth Industry Bootcamp (YIB) Programme which gathers young talents from the schools is a platform that instils in them the interest and to understand the essentials of science for future demands.